Strategi Pengembangan Desa Wisata Berbasis Pemberdayaan Masyarakat: Tourism Village Development Strategy Based on Community Empowerment - Albert, Steffan; Mubarokah, Mubarokah; Setiawan, Risqi Firdaus (Jurnal Ilmiah Manajemen Agribisnis, 2024)
The concept of community-based tourism village development is that all activities carried out must be based on, from, and for the community. The purpose of this study was to describe the process of community empowerment through the management of Jambu Tourism Village and to formulate a strategy for developing a tourism village. The research method used was descriptive analysis and SOAR matrix analysis. The results of the study showed that the process of community empowerment in Jambu Tourism Village had three stages, namely the awareness stage through the socialization process; the capacity building stage consisted of providing guidance and training, the formation of the BUMDes Jaya Makmur organization, and the empowerment stage consisted of community involvement both in the role of the organization and the implementation of activities in Jambu Tourism Village. The main strategy that can be suggested based on the SOAR matrix analysis functions to compile strategic factors that describe how strength can be determined by the SA (Strength-Aspiration) strategy, namely using strength to realize aspirations, meaning that Jambu Tourism Village must strengthen in the field of increasing the quantity and quality of tourist attractions by combining traditional village nuances with contemporary touches, strengthening in services to visitors and maximizing the use of social media.